The performance of the Health of the Nation Outcome Scales as measures of clinical severity. (30th May 2016) - Müller, Mario; Vandeleur, Caroline; Weniger, Godehard; Prinz, Susanne; Vetter, Stefan; Egger, Stephan T.
Abstract: The aim of this study was to examine the performance of the Health of the Nation Outcome Scales (HoNOS) against other measures of functioning and mental health in a full three-year cohort of admissions to a psychiatric hospital. A sample of N=1719 patients (35.3% females, aged 17–78 years) was assessed using observer-rated measures and self-reports of psychopathology at admission. Self-reports were available from 51.7% of the sample (34.4% females, aged 17–76 years). Functioning and psychopathology were compared across five ICD-10 diagnostic groups: substance use disorders, schizophrenia and psychotic disorders, affective disorders, anxiety/somatoform disorders and personality disorders. Associations between the measures were examined, stratifying by diagnostic subgroup. The HoNOS were strongly linked to other measures primarily in psychotic disorders (except for the behavioral subscale), while those with substance use disorders showed rather poor links. Those with anxiety/somatoform disorders showed null or only small associations. This study raises questions about the overall validity of the HoNOS. It seems to entail different levels of validity when applied to different diagnostic groups. In clinical practice the HoNOS should not be used as a stand-alone instrument to assess outcome but rather as part of a more comprehensive battery including diagnosis-specific measures. Highlights: This is the first study to examine the validity of the German version of the HoNOS in a very large clinically diverse sample. The HoNOS was linked to measures of functioning while associations with self-reported psychopathology were controversial. The HoNOS was not linked to functioning in patients with anxiety or somatoform disorders. The links with functioning were particularly strong in psychotic patients but rather low in patients with substance misuse. The HoNOS should rather be used in conjunction with diagnosis-specific measures in clinical practice.